EKSPLORASI DAN PRODUKTIFITAS PADANG PENGGEMBALAAN DI KECAMATAN PAMONA TIMUR KABUPATEN POSO SULAWESI TENGAH - Karti, P.D.M.H.; Abdullah, L.; Prihantoro, I. (Pastura, 2015)
Pasture in District of East Pamona, Poso Regency has potential as forage for livestock.. This study was conducted in two villages (Didiri and Kelei) to explore of plant species as feed and productivity calculation such as botanical composition and carrying capacities. Type of grasses that grow are Sporobolus sp, Paspalum sp, Paspalum cartilagineum, Axonopus compresus, Euleusine indica. Type of legumes that grow are Stylosanthes guianensis, Desmodium sp, Centrocema pubescens, Callyandra callothyrsus, Leucaena leucocephala. Types of weeds have started to grow in several locations within the region, such as Melastoma, Mimosa pudica, Imperata cylindrica, Cromolena odorata, Cyperacea, and Lamtana camara. Botanical composition (%) in Kelei for grass, legumes, weeds (84.76: 6.75: 8:49) and Didiri for grass, legumes, weeds (95.34: 0:51: 4.15). Carrying Capacities in Kelei and Didiri was 0.96 ± 0:23 and 1:12 ± 0:29 ST / ha.
Keywords: pasture; carrying capacities; botanical composition; grass; legume